A realistic concept of a manned Mars mission with nuclear–electric propulsion. (November 2015) - Loeb, H.W.; Petukhov, V.G.; Popov, G.A.; Mogulkin, A.I.
Abstract: Based on state-of-the-art technique and recent developments, it would be feasible to send some cosmonauts to Mars around 2035. The key to this enterprise is the nuclear–electric in-space propulsion (NEP). In 2010, the development of the 1 MWe nuclear space power plant as well as of the ion thrusters with the ion beam diameter of 50 cm and specific impulse of 7000 s was started at the Keldysh Research Center in Moscow. With regard to thrusters, the Keldysh Research Center cooperated with the Moscow Aviation Institute. According to our analysis, a cluster of ion thrusters (each of 50 kW in power) with three 1 MW reactors could propel a 250-tons vehicle with four cosmonauts on board to Mars and back. The mission architecture would be quite straightforward: the still unmanned spaceship will be assembled in the 800 km LEO and then spiraled up by NEP into the 200, 000 km launch orbit. There, the chemical crew transport vehicle will arrive and dock. The interplanetary journey to Mars will require 337 days. On its arrival to Mars, the spaceship will spiral down into the 500 km parking orbit. Then, a 65 ton descent/ascent vehicle with three or four cosmonauts will leave the NEP vehicle and land. After 218 days, the excursion team will return to the mothership for the homebound trip. At the Earth approach, the cosmonauts will change to the crew transport vehicle, descend and land, whereas the burnt-out ship will be lost in space. It is true that one single spaceship is able to accomplish the mission. However, an international fleet of two or three manned ships together with a cargo ship would be recommendable, not only with regard to the volume of scientific results and a risk reduction, but also to demonstrate solidarity of mankind. Highlights: Possibility of manned Mars mission is proved. Required performance of rf-ion thrusters making such mission realistic are presented. Mars mission analysis was made and mass balance is presented.